2018
DOI: 10.1007/s10518-018-00543-7
|View full text |Cite
|
Sign up to set email alerts
|

A new energy-absorbing system for seismic retrofitting of frame structures with slender braces

Abstract: Past earthquakes experience regarding frame structures with slender braces, i.e. tensiononly concentrically braced frames, has demonstrated poor seismic behavior of these systems. In these buildings, the bracing system does not have sufficient buckling strength, and the sudden buckling causes rapid drops in the structural stiffness and strength. In the present study, to improve the seismic performance of slender braces in frame structures, adding new, replaceable shear-flexural yielding hinges in the central y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Among hysteretic dampers, devices based on the plastic deformation of mild steel are the most popular due to their stability at high levels of deformation, negligible degradation and reliability during repeated cycles, and good resistance to weathering and aging. Different types of steel dampers have been proposed and tested for implementation in structures (Javanmardi et al 2020;Di Cesare et al 2014;2017b;Pampanin et al 2017;Morillas et al 2020;Mohsenian et al 2018), including torsional or flexural beams (Montuori et al 2015), single-axis dampers (Skinner et al 1974) U-strips (Baird et al 2014;Buchanan et al 2007), buckling-restrained braces (BRB) (Watanabe et al 1988;Foti et al 2020), crescent shaped braces (CSBs) (Palermo et al 2014(Palermo et al , 2015(Palermo et al , 2017Kammouh et al 2018), and energy dissipative steel cushions (Ozkaynak et al 2018;Gullu et al 2019). In parallel to the development of the hardware, viable design procedures and configurations of dissipative bracing systems incorporating metallic dampers have been envisaged for the seismic retrofitting of existing r.c and steel buildings (Akcelyan et al 2016;Barbagallo et al 2017;Bergami et al 2013;Di Cesare et al 2017a;Durucan et al 2010;Mazza et al 2015a;2015b;2016a, b;Nuzzo et al 2019;O'Reilly et al 2016;Gandelli et al 2019;Mohammadi et Al.…”
Section: Introductionmentioning
confidence: 99%
“…Among hysteretic dampers, devices based on the plastic deformation of mild steel are the most popular due to their stability at high levels of deformation, negligible degradation and reliability during repeated cycles, and good resistance to weathering and aging. Different types of steel dampers have been proposed and tested for implementation in structures (Javanmardi et al 2020;Di Cesare et al 2014;2017b;Pampanin et al 2017;Morillas et al 2020;Mohsenian et al 2018), including torsional or flexural beams (Montuori et al 2015), single-axis dampers (Skinner et al 1974) U-strips (Baird et al 2014;Buchanan et al 2007), buckling-restrained braces (BRB) (Watanabe et al 1988;Foti et al 2020), crescent shaped braces (CSBs) (Palermo et al 2014(Palermo et al , 2015(Palermo et al , 2017Kammouh et al 2018), and energy dissipative steel cushions (Ozkaynak et al 2018;Gullu et al 2019). In parallel to the development of the hardware, viable design procedures and configurations of dissipative bracing systems incorporating metallic dampers have been envisaged for the seismic retrofitting of existing r.c and steel buildings (Akcelyan et al 2016;Barbagallo et al 2017;Bergami et al 2013;Di Cesare et al 2017a;Durucan et al 2010;Mazza et al 2015a;2015b;2016a, b;Nuzzo et al 2019;O'Reilly et al 2016;Gandelli et al 2019;Mohammadi et Al.…”
Section: Introductionmentioning
confidence: 99%
“…In the next step, assuming a lognormal distribution for the response values, after calculating As schematically shown in Fig. 15a, by replacing a value for X 0 as the response corresponding to a specific performance level, the area under the density function from −∞ to X 0 denotes the reliability, which means that at this level of intensity, to probability of P, the response parameter will not reach the limit values corresponding to this damage level Mohsenian and Mortezaei 2018a). Finally, P 0 represents the fragility probability that specifies the likeliness of experiencing the specified damage level at this level of intensity (P 0 = 1−P).…”
Section: Reliability Analysis Of the Frames Individually For The Storeysmentioning
confidence: 99%
“…The stable hysteretic curves and high energy dissipation capacity are counted as the most notable features of this system, leading to satisfactory performance under strong seismic excitations (Baradaran et al 2015;Bouwkamp et al 2016;Vetr et al 2017). Given the fact that vertical links can act as a seismic fuse, the majority of the earthquake energy is absorbed by these elements, and consequently, the other structural members generally remain in their linear phase of behaviour (Zahrai and Mahroozadeh 2010;Mohsenian and Mortezaei 2018a;. This implies that, unlike conventional EBF systems, the beam elements and slabs are not affected by the link rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Research carried out on EBF systems with vertical links showed that the seismic energy acting on such systems can be entirely dissipated by the vertical links while the remaining structural elements (i.e. beams, columns and braces) remain in elastic or near elastic state [4,20]. Therefore, the vertical links can be designed as replaceable elements equipped with high ductility and energy absorption capacity.…”
Section: Introductionmentioning
confidence: 99%